Precision Solar Spectrum Filtering in Aerogel Windows via Synergistic ITO-Ag Nanoparticle Doping for Hot-Climate Energy Efficiency - Huilin Yang; Maoquan Huang; Mingyang Yang; Xuankai Zhang; Mu Du (Gels)
Windows are a major contributor to energy loss in buildings, particularly in hot climates where solar radiation heat gain significantly increases cooling demand. An ideal energy-efficient window must maintain high visible light transmittance while effectively blocking ultraviolet and near-infrared radiation, presenting a significant challenge for material design. We propose a plasma silica aerogel window utilizing the local surface plasmon resonance effect of plasmonic nanoparticles. This design incorporates indium tin oxide (ITO) nanospheres (for broad-band UV/NIR blocking) and silver (Ag) nanocylinders (targeted blocking of the 0.78–0.9 μm NIR band) co-doped into the silica aerogel. This design achieves a visible light transmittance of 0.8, a haze value below 0.12, and a photothermal ratio of 0.91. Building simulations indicate that compared to traditional glass, this window can achieve annual energy savings of 20–40% and significantly reduce the economic losses associated with traditional glass, providing a feasible solution for sustainable buildings.